Association between C3435T polymorphism of MDR1 gene and the incidence of drug-resistant epilepsy in the population of Polish children. Issue 1 (December 2016) - Stasiołek, Mariusz; Romanowicz, Hanna; Połatyńska, Katarzyna; Chamielec, Maciej; Skalski, Dominik; Makowska, Marianna; Smolarz, Beata
Abstract Purpose Epilepsy is a disease of neurological character. Approximately one third of epileptic patients demonstrate a drug-resistant phenotype, which is associated with the development of drug-resistant epilepsy. The multidrug resistance protein 1 and glycoprotein P, encoded byMDR1, play a significant role in the transmembrane transport of anti-epileptic agents. Single nucleotide polymorphism C3435T (rs1045642) withinMDR1 gene may be associated with an increased expression of P-gp which affects the levels of antiepileptic drugs in plasma. The presented studies analysed the association between C3435T polymorphism ofMDR1 gene and the incidence of drug-resistant epilepsy in the population of Polish children. Methods C3435T polymorphism ofMDR1 gene was analysed by the high resolution melting technique in a group of patients with drug-resistant (n = 106) and drug-responsive epilepsy (n = 67), as well as in non-epileptic children (n = 98) hospitalised at the Department of Neurology, Polish Mother's Memorial Hospital in Lodz. Genotype and allele distributions were evaluated and their compatibility with the Hardy–Weinberg distribution was assessed by means of the χ2 test. Genotype and allele evaluation, regarding their relationship with a given feature, was supported by an analysis of odds ratio and 95 % confidence interval, calculated according to the logistic regression model. Results An association was observed between the incidence rate of DRE and the presence of C allele in C3435T polymorphism ofMDR1 gene, which may enhance the risk of the disease. The T allele may then play a protective role. No differences were found in the studied groups, regarding either genotype or allele distribution in reference to patient's gender or concomitant diseases. Conclusion Following the obtained results, C3435T polymorphism ofMDR1 gene may be connected with the incidence of drug-resistant epilepsy in the population of Polish children. ISRCTN ISRCTN73824458. Registered 28th September 2014.